Biomarker Significance of Interleukin-18 in Juvenile Idiopathic Arthritis - Al-bassam , Wasan W.; Ad'hiah, Ali H.; Mayouf , Khadier Z. (Iraqi Journal of Science, 2020)
Juvenile idiopathic arthritis (JIA) represents a group of multifactorial autoinflammatory arthritis diseases. A dysregulated production of pro-inflammatory cytokines is proposed to have a role in the pathogenesis of the disease. Interleukin-18 (IL-18) is one of these pro-inflammatory cytokines. Therefore, this study aimed to define the role of IL-18 in the pathogenesis of JIA. Accordingly, the serum level of IL-18 was determined in 59 Iraqi JIA patients and 58 matched controls. The results revealed a significantly increased median of IL-18 in the patients as compared to the control. A similar increased level was observed in subgroups of patients characterized according to gender, seropositivity for C-reactive protein and rheumatoid factors, juvenile arthritis disease activity score 27 (JADAS27), type of medication, and JIA subtypes. However, JADAS27 showed a significant positive correlation with IL-18 level. Receiver operating characteristic analysis revealed that IL-18 occupied a significant area under the curve, and therefore its significance as a biomarker was suggested. In conclusion, IL-18 is an important biomarker for JIA and may have a role in pathogenesis of disease.